Customer referencing and capital market benefits: Evidence from the cost of equity - Jing, Jiao; Myers, Linda A.; Ng, Jeffrey; Su, Lixin (Nancy) (Contemporary Accounting Research, 2023)
Abstract Customer referencing is a strategy that firms can use to disclose their connections with reputable customers as a means of enhancing their own reputations. We study the capital market benefits of naming reputable nonmajor customers in firms' financial reports to provide empirical evidence on whether this form of customer referencing has important practical implications. We predict and find that firms enjoy a lower cost of equity when they engage in customer referencing in their financial reports, consistent with the argument that this form of voluntary disclosure increases investor attention and customer certification. In cross‐sectional analyses, we predict and find that the benefits of customer referencing are more pronounced for firms that (1) lack major customers or reputable major customers, (2) name customers whose reputations exceed their own, and (3) face higher competition. Overall, our study provides evidence that communicating certain interorganizational connections can generate capital market benefits for disclosing firms.